The use of military force in the management and conflict resolution - Oliveira, António (2016)
The end of the Cold War changed the paradigm of the role and scope of military force in the management and resolution of conflicts. With increasing intervention by the international community, the new generation of peacekeeping operations has adopted a multidimensional approach to military force to be used in coordination with other instruments of power, ensuring a proper strategic framework considering the desired end state. This new approach and the increasing complexity of conflicts, predominantly intrastate in nature, have led on the one hand to understandings of the traditional principles of peace operations being addressed, and on the other to military forces facing diverse challenges. The most complex is related to the effective use of combat capabilities, as it seems that there is a lack of political will, after making the deployment of forces, to ensure their effective use. However, the effective use of force being the most critical element, but simultaneously more differentiating and characterising of the use of the military instrument, the management and resolution of conflicts has elevated the range of capabilities of military forces that goes beyond traditional capabilities combat, showing themselves useful in support, complement or replacement of non-military capabilities.